The urradiology in the diagnosis of pelvic disorders: conclusions Juan C Lorenzo - Schenone, Héctor (Cirugía del Uruguay, 1971)
First of all, we must briefly refer to the visceral injuries that most frequently result in the course of such trauma. They are the following: intraperitoneal rupture of the bladder, subperitoneal rupture, and posterior urethral rupture.